2018
DOI: 10.1177/0093854818802876
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Job Expectations, Workload, and Autonomy on Work-Related Stress Among Prison Wardens in the United States

Abstract: Prison wardens manage both external pressures and internal challenges that affect work-related stress. Using data from a national survey of prison wardens, we examined the impact of conflicting job expectations, workload, and job autonomy on work-related stress among prison wardens. The ordered logistic regression results showed a significant and positive relationship between conflicting job expectations and work-related stress. The results also showed a significant and positive relationship between unmanageab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
(96 reference statements)
1
19
1
1
Order By: Relevance
“…Job autonomy is one of the job resources that can help employees cope with job demands (Van Yperen et al, 2016 ) by allowing them to make their own decisions about when and how to respond to the demands (Gao & Jiang, 2019 ). Employees who have greater job autonomy are likely to feel more free from external constraints (Deci et al, 1989 ), to handle work stress better (Jiang et al, 2020 ; Schiff & Leip, 2019 ), and to experience less work burnout (Ahuja et al, 2007 ; Bakker et al, 2005 ), all of which also lead to higher job satisfaction (Yeh, 2015 ; Yucel, 2018 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Job autonomy is one of the job resources that can help employees cope with job demands (Van Yperen et al, 2016 ) by allowing them to make their own decisions about when and how to respond to the demands (Gao & Jiang, 2019 ). Employees who have greater job autonomy are likely to feel more free from external constraints (Deci et al, 1989 ), to handle work stress better (Jiang et al, 2020 ; Schiff & Leip, 2019 ), and to experience less work burnout (Ahuja et al, 2007 ; Bakker et al, 2005 ), all of which also lead to higher job satisfaction (Yeh, 2015 ; Yucel, 2018 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Hence, it is reasonable to assume that job autonomy, as a job resource, is key to the success of an organization, and employees who have more autonomy in their work are more likely to experience job satisfaction as they can freely make their own decisions. When employees have more autonomy in their work, they can handle work stress better (Schiff and Leip 2019 ). Further, job satisfaction often surveyed in the context of the results of work–family conflicts (WFCs; Grandey et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a considerable number of empirical studies have shown a positive link between workload and stress (e.g. Schiff & Leip, 2019;Suarthana & Riana, 2016). The mechanism of producing stress through workload is usually explained by the dimensions of quantitative workload and qualitative workload .…”
Section: Intrinsic Job Characteristicsmentioning
confidence: 99%
“…authority of making decisions at work) is positively related to emotional fatigue and worry (M.-Y. Leung et al, 2010;Schiff & Leip, 2019).…”
Section: Organisational Factorsmentioning
confidence: 99%